Business Entity Pre-Merger Notification Policy as Law Enforcement in the Industrial Revolution Era 4.0 - Ibrahim Suhandi, Farid (Universitas Negeri Semarang, 2019)
The consequence of the dynamics of globalization has given rise to an a priori phenomenon called the industrial revolution 4.0 so that this is a challenge for the Business Competition Supervisory Commission (KPPU) to be able to protect market conditions that develop as dynamically as possible. Through this matter, the authority of KPPU needs to be optimized in order to adjust to market dynamics. The implementation of a company merger becomes a situation that has the potential to cause a form of unfair business competition. This is certainly the authority of KPPU to be able to provide supervision and evaluation of this matter, but with the post-merger notification regime still in force, it is possible that there will be a cancellation of a merger which has an impact on losses suffered by the company. Therefore, it is necessary to change the regime to pre-notification of merger which has gone through several necessary considerations. Thus, it is hoped that KPPU will be able to become the main protector in creating a fair and conducive market condition.